Merdeka curriculum and English language learning: A qualitative exploration in a secondary school - Nurlaily Nurlaily; Maya Marsevani; Tetti Tetti; Raswita Raswita; Hardy Christ (Universitas Muhammadiyah Malang, 2026)
This study explores the implementation of the merdeka curriculum in English language teaching at a senior high school in Batam, with particular attention to teaching strategies, classroom management practices, and challenges experienced by both teachers and students. Employing a descriptive qualitative research design, data were collected through classroom observations and semi-structured interviews involving two English teachers and three students who actively participated in the learning process under the merdeka curriculum framework. The data were analyzed using thematic analysis to identify recurring patterns and key themes. The findings reveal that teachers employed various student-centered strategies, including language games, group discussions, presentations, and the integration of digital tools such as Kahoot and Liveworksheet to enhance student engagement. However, the effectiveness of these strategies was constrained by several factors, including diverse student proficiency levels, limited access to digital devices, unstable internet connectivity, and students’ insufficient readiness for independent learning. Classroom management also emerged as a challenge, particularly in maintaining student focus during group activities and ensuring smooth transitions between learning tasks. The study concludes that while the merdeka curriculum provides flexibility and opportunities for innovative teaching practices, its successful implementation depends on adequate teacher training, strong institutional support, and sufficient technological infrastructure. The findings imply that schools should strengthen professional development programs focusing on differentiated instruction and independent learning skills to optimize the effectiveness of the merdeka curriculum in English language learning contexts.